2020
DOI: 10.1186/s13018-020-01793-5
|View full text |Cite
|
Sign up to set email alerts
|

A propensity score-matched analysis comparing outpatient and short-stay hospitalization to standard inpatient hospitalization following total ankle arthroplasty

Abstract: Background: Given the trend toward value-based care, there has been increased interest in minimizing hospital length of stay (LOS) after orthopedic procedures. Outpatient total ankle arthroplasty (TAA) has become more popular in recent years; however, research on surgical outcomes of this procedure has been limited. This study sought to employ large sample, propensity score-matched analyses to assess the safety of outpatient and short-stay discharge pathways following TAA. Methods: The ACS NSQIP database was u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…While reasons for a prolonged hospital stay are certainly numerous, prior literature has demonstrated a clear association between increased length of stay and suboptimal outcomes following TAA. 14,15 Our data contributes to a mixed body of literature on race and its effect on hospitalization length after TAA. In a study utilizing the NIS (National Inpatient Sample) database, Singh and Cleveland reported a significantly higher rate of prolonged hospital stays in black and Hispanic TAA patients compared to white patients.…”
Section: Discussionmentioning
confidence: 78%
“…While reasons for a prolonged hospital stay are certainly numerous, prior literature has demonstrated a clear association between increased length of stay and suboptimal outcomes following TAA. 14,15 Our data contributes to a mixed body of literature on race and its effect on hospitalization length after TAA. In a study utilizing the NIS (National Inpatient Sample) database, Singh and Cleveland reported a significantly higher rate of prolonged hospital stays in black and Hispanic TAA patients compared to white patients.…”
Section: Discussionmentioning
confidence: 78%
“…There is, howevera lack of evidence around other major procedures such as ankle fusions being performed as day-case. The safety of outpatient compared with inpatient ankle surgery is comparable and therefore they suggest that outpatient ankle surgeries should be considered for patients that are suitable[ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“… 26 Another investigation indicated that outpatient and short-stay discharge do not inherently increase the incidence of short-term complications and poor outcomes relative to standard inpatient hospitalization after TAA. 20 Neither of these studies evaluated the factors predictive of early complications. The present study indicates outpatient TAA is not associated with increased risk of complications, reoperation, or readmission, which reinforces previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…The present study indicates outpatient TAA is not associated with increased risk of complications, reoperation, or readmission, which reinforces previous findings. 20 , 26 The finding of increased 30-day readmission in patients undergoing TAA as an inpatient prompted evaluation of factors predictive of complications, reoperation, and readmission. These results will serve to guide patient selection for TAA and performance of this procedure on an outpatient basis.…”
Section: Discussionmentioning
confidence: 99%